Impact of salinity on seed germination and antioxidative profile of tomato leaves (Solanum lycopersicum L. cv.MT1) - A. Shanab, Asma Abubaker (2016)
Salinity is a serious problem in many parts of the world that limits the productivity of agricultural crops. Even though, it is one of the major abiotic stresses that affect almost every aspect of physiology and biochemistry of plants but at certain amount could be beneficial to plant. Many studies had been done to determine the effects of salt stress towards the morphology, physiology, biochemistry and productivity of tomato plant but study on germination and antioxidant activity on tomato plants is still limited. This work aimed to study the effects of NaCl on the germination, histological of seedling leaves, and antioxidant profiling of Solanum lycopersicum cv. MT1. A 20 surface sterilized of tomato MT1 seeds were germinated in sterilized petri dishes and treated with 6 ml of 1, 3, 5, 10, 15, 30 mM NaCl separately and deionized water used as a control to study the effects of NaCl on tomato seed germination. Plates were sealed with parafilm to prevent evaporation followed by placed in Random Block Design in the growth room at 25˚C and 16/8 h (light / dark) for 10 days. Seeds were considered germinated when radicle had extended at least 2 mm. The water uptake, germination percentage (% GP), seed vigor, salt tolerance, length of hypocotyl and radical, and biomass of seedlings were measured. Results found that the germination of MT1 seed adversely delayed and decreased as NaCl concentration increased. The water uptake, germination percentage, seed vigor and salt tolerance decreased when the concentration of NaCl increased except 3 mM NaCl showed the highest germination percentage (87.5%) and vigor (11.4). The water uptake, seed vigor and salt tolerance decreased when as the increased of NaCl. The response of hypocotyls and radical under NaCl treatment are different which is not significantly (ANOVA, P<0.05) affected the length of hypocotyl but significantly reduced the radical length (ANOVA, P<0.05) except in 3 mM NaCl. NaCl increase the seedling length up to 3 mM (13 cm). Increased NaCl concentration not significantly (ANOVA, P<0.05) reduced the shoot dry weight (ANOVA, P<0.05), on other hand, the root dry weight reduce significantly (ANOVA, P<0.05) as NaCl concentration higher. At day 10, seedling leaves were collected from control, 10 and 30 mM NaCl and fixed for histological studies. Histological of seedlings leaves highly affected by NaCl concentration. The entire structural of histological seedling leaves highly disrupted as NaCl concentration increased as can be compared between 10 mM and 30 mM NaCl. The structure of epidermis cells on both epidermal layers totally changed. Moreover, the arrangement of mesophylls tissues was also in disorder. A major reduction in veins tissue dimensions were observed and this lead on its ability to conduct water and nutrients into seedlings system. To study the effects of NaCl to the antioxidant profiling of tomato plant. Four different concentration of NaCl treatment which is 5, 10, 15 and 30 mM and deionized water as a control was used. 21 days old seedlings were planted in the pots containing 1 kg of mix soil (3 top soil: 1 sand). Each treatment has 6 replicates. The seedlings were watered with 100 ml of NaCl and alternate with 100 ml ultra-pure water every 3 days for six weeks. After 6 six weeks, total chlorophyll, total phenolic, flavonoid and proline and anti-oxidative activity were measured. Results showed that NaCl increase total chlorophyll, total phenolic, flavonoid and proline and anti-oxidative activity. Total chlorophyll found higher in 15 and 30 Mm NaCl which is 41.7 mg and 39.6 mg/0.1 g compared with control plant only 24.1 mg/0.1 g. Results showed an increasing of total phenolic, flavonoid, and proline content with increasing of NaCl. The highest amount of phenolic and flavonoid achieved at 15 mM NaCl higher than the control plant and other treatment. Results also found that total proline increase as NaCl increased. 15 and 30 mM NaCl show higher total proline content which is 0.041 and 0.044 mg/0.1g compared with control (0.016 mg/0.1g) and other NaCl treatment. The maximum of DPPH and reducing power activity were observed in the 5 mM NaCl while antioxidant reduced as NaCl increase up to 30 mM NaCl. As conclusion, raising the concentration of NaCl had adversely affected on the germination and early growth of seedlings (except 3 mM NaCl). The histological of MT1 seedlings leaves highly affected by NaCl. Treatment tomato plants with moderate concentration of NaCl able to increase the antioxidative properties and activity of tomato plant.